PENGARUH KOMBINASI FOSFAT ALAM DENGAN PUPUK NITROGEN DAN KALIUM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L) - Eso Solihin; Rija Sudirja; Stefina Liana Sari; Anni Yuniarti (JURNAL AGRO NUSANTARA, 2025)
Phosphorus is one of the essential macronutrients that plays a crucial role in the growth and productivity of maize (Zea mays L.). The use of natural phosphate as an alternative phosphorus source, when combined with nitrogen (urea) and potassium (KCl) fertilizers, has the potential to enhance crop yield. This study aimed to evaluate the effect and determine the optimal dosage of natural phosphate in combination with urea and KCl on the growth and yield of maize. The experiment was conducted from February to May 2025 using a Randomized Complete Block Design (RCBD) with the following treatments: A (control), B (single NPK), C; (1/4 P) + NK, D; (1/2 P) + NK, E; (3/4 P) + NK, F; (1 P) + NK, G; (1 1/4 P) + NK, H; (1 1/2 P) + NK, I; (1 3/4 P) + NK dan J; (2 P) + NK. The results showed that the combination of natural phosphate with urea and KCl had a significant effect on all growth parameters and corn yields. The highest results were obtained by providing 225 kg/ha of natural phosphate, 300 kg/ha of urea, and 150 kg/ha of KCl, with a corn yield of 16.04 tons/ha.